2007
DOI: 10.1073/pnas.0706695104
|View full text |Cite
|
Sign up to set email alerts
|

An inducible lambdoid prophage encoding cytolethal distending toxin (Cdt-I) and a type III effector protein in enteropathogenic Escherichia coli

Abstract: Cytolethal distending toxins (CDTs) are inhibitory cyclomodulins, which block eukaryotic cell proliferation and are produced by a diverse group of Gram-negative bacteria, including Escherichia coli strains associated with intestinal and extraintestinal infections. However, the mode of transmission of the toxin gene clusters among diverse bacterial pathogens is unclear. We found that Cdt-I produced by enteropathogenic E. coli strains associated with diarrhea is encoded by a lambdoid prophage, which is inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 29 publications
5
61
0
1
Order By: Relevance
“…E. coli is unique amongst CDTproducing bacteria in that at least five divergent variants of CdtB have been found within this single species so far, which also differentially segregate according to E. coli pathotypes ( Degnan & Moran, 2008). Indeed, carriage of the CDT operon by certain enteropathogenic E. coli with EcolCdtB-I on a lysogenic phage background mediates HGT among related species, and confers enhanced bacterial toxicity during phage induction (Asakura et al, 2007a;Johnson et al, 2007; Oswald et al, 1994; Pérès et al, 1997;Tó th et al, 2009). Also unique to E. coli is the location of the operon encoding EcolCdtB-III which is found on a large conjugative plasmid called pVir (Johnson et al, 2010).…”
Section: Cdt Operonmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli is unique amongst CDTproducing bacteria in that at least five divergent variants of CdtB have been found within this single species so far, which also differentially segregate according to E. coli pathotypes ( Degnan & Moran, 2008). Indeed, carriage of the CDT operon by certain enteropathogenic E. coli with EcolCdtB-I on a lysogenic phage background mediates HGT among related species, and confers enhanced bacterial toxicity during phage induction (Asakura et al, 2007a;Johnson et al, 2007; Oswald et al, 1994; Pérès et al, 1997;Tó th et al, 2009). Also unique to E. coli is the location of the operon encoding EcolCdtB-III which is found on a large conjugative plasmid called pVir (Johnson et al, 2010).…”
Section: Cdt Operonmentioning
confidence: 99%
“…E. coli is unique amongst CDTproducing bacteria in that at least five divergent variants of CdtB have been found within this single species so far, which also differentially segregate according to E. coli pathotypes (Table 2; Janka et al, 2003). Since it is presently unknown whether or not the genes encoding the CdtA and CdtC subunits display sequence divergence similar to their corresponding CdtB variants, and until this can be resolved, we propose to designate these toxins as EcolCdtB-I to -V. Similar to other CDT-producing bacteria, EcolCdtB-I, -II, -IV and -V are encoded by chromosomal gene loci (Asakura et al, 2007a;Johnson et al, 2007;Oswald et al, 1994;Pérès et al, 1997;Tó th et al, 2009). However, analyses of sequences upstream and downstream of operons encoding EcolCdtB-I and -IV variants revealed lambdoid prophage genes (Asakura et al, 2007a;Tó th et al, 2009), whereas homologues of bacteriophages P2 and lambda are found in E. coli strain O157 : H 2 493/89 harbouring EcolCdtB-V (Janka et al, 2003).…”
Section: Cdt Operonmentioning
confidence: 99%
“…Epidemiological studies from elsewhere have detected only a low frequency of CLDTEC and an association of this toxin with EPEC or EHEC-linked serovars. The role of this toxin in human disease remains to be established and rather than a distinct category, CLDTEC may represent other pathotypes that are converted by lysogenization with a cdtbearing lambdoid phage [242].…”
Section: Other Potentially Diarrheagenic E Coli Categoriesmentioning
confidence: 99%
“…At least five different cytolethal distending toxins have been described in E. coli, and type I is phage borne [240][241][242]. Only two African studies have sought cytolethal distending toxinproducing E. coli (CLDTEC).…”
Section: Other Potentially Diarrheagenic E Coli Categoriesmentioning
confidence: 99%
“…CDTs are quite disseminated in several species and so far in E. coli fi ve genotypes were identifi ed (reviewed by Tóth and Sváb) [7]. In all cases the cdtABC operons were either part of the genome of an inducible converting lambdoid prophage [8], a defective P-2 like prophage [9], a large plasmid [10], as part of a PAI [11] or framed with lambdoid phage genes [12].…”
Section: Introductionmentioning
confidence: 99%